A Comparison of Conjunctive Cohesion between Pakistani and British English Newspapers’ Opinion Articles - Maham Khalid; Humaira Irfan (University of Chitral Journal of Linguistics and Literature, 2024)
Pakistani English has been forming and developing norms different from standard British/American English. This study explores the use and patterns of conjunctive cohesion, as elaborated and categorized by Halliday and Hasan (1976) and revised by Halliday and Matthiessen (2013) in Pakistani and British Newspapers’ Opinion Articles from November 2023. Twenty-eight opinion articles from the Pakistani English newspaper ‘The Express Tribune (TET)’ and 25 from the British English newspaper ‘The Guardian (TG)’ were collected and saved into two separate text files for analysis. Frequencies of 80 conjunctions (which are categorized into three categories: elaboration, extension, and enhancement; and further into nine subcategories) were calculated by Anthony’s (2023) AntConc software (version 4.2.4). Pakistani data showed a higher frequency of Extending Conjunctions than British data. However, the use of both elaborating and enhancing conjunctions is higher in British writing than in Pakistani writing. The study revealed extending conjunctions (‘and,’ ‘but,’ ‘or’ being the top 3 in both data) as the most used items by Pakistani and British writers; results also suggested excessive use of ‘and’ among Pakistani writers. Yet when it comes to complex conjunction items, the cohesive choices of both Pakistani and native English writers show differences.